The Synergistic Impact of Astrocyte Reactivity and Vitamin D Deficiency on Post-Stroke Cognitive Impairment: A Systematic Review and Meta-Analysis - Patricia; Anak Agung Ayu Putri Laksmidewi; Kumara Tini (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Post-stroke cognitive impairment (PSCI) is a common, debilitating outcome of ischemic stroke. Glial Fibrillary Acidic Protein (GFAP), marking astrocyte reactivity, and Vitamin D, a neuro-immunomodulatory steroid, are independently linked to PSCI. This study aimed to quantify the synergistic impact of elevated serum GFAP and concurrent Vitamin D deficiency on PSCI risk. Methods: Following PRISMA guidelines, a systematic search of PubMed, Scopus, and Web of Science was conducted for prospective cohort studies (2015-2025) assessing acute serum GFAP, 25-hydroxyvitamin D (25(OH)D), and subsequent cognitive outcomes in ischemic stroke patients. Quality was assessed using the Newcastle-Ottawa Scale. A meta-analysis of seven studies (n=3,850) was performed using a random-effects model to calculate pooled odds ratios (ORs) for PSCI across four biomarker-defined groups. A formal test for synergistic interaction was conducted by assessing the departure from additivity of effects on the log-odds scale. Results: Seven high-quality studies were included. Compared to the reference group (Normal GFAP/Sufficient Vitamin D), the pooled OR for PSCI was 2.18 (95% CI: 1.85-2.57) for high GFAP alone and 1.95 (95% CI: 1.65-2.30) for Vitamin D deficiency alone. For the dual-biomarker group (High GFAP/Deficient Vitamin D), the pooled OR was 4.75 (95% CI: 3.98-5.67). This observed risk was significantly greater than the 3.13 OR expected from a purely additive model (p for interaction < 0.001), confirming a significant synergistic effect. Sensitivity analysis showed the effect was most pronounced in patients with moderate-to-severe strokes (NIHSS > 5). Conclusion: Elevated serum GFAP and Vitamin D deficiency synergistically increase the risk of PSCI, particularly in patients with more severe strokes. The interplay between acute astroglial injury and compromised systemic neuroprotection appears to be a critical determinant of cognitive outcomes. While confounding by patient frailty requires further study, this dual-biomarker profile identifies a high-risk subgroup and highlights a key pathophysiological interaction.